PWE-432 Learning curve for upper gi endoscopy – qualitative assessment of developmental phases of novice trainees. (22nd June 2015) - Axe, K; Hawkes, E; Turner, J; Hurley, J; Neville, P; Warren, N; Hawkes, N
Abstract : Introduction: JETS e-portfolio provides data on learning curves in UK trainees, 1 but to improve outcomes requires a detailed understanding of training needs at each point on the curve. We mapped learning needs of novice trainees in upper GI endoscopy (UGIE), investigating stages of practical and cognitive skills development. Method: A Structured Programme of Induction and Training (SPRINT) in UGIE, delivered training sessions at months 0, 1, 2 and 4, (simulators, lesion recognition (LR), JAG Basic UGI course &hands-on training). At 4 months semi-structured interviews explored all 7 trainee's experience, focussing on key stages where learning needs changed. A deductive approach to analysis using a modified grounded theory approach 2 was followed. Results: Novices identified distinct phases in the development of endoscopic skills 1) Technical unimodal (high effort); 2) Bimodal (technical + cognitive framework initiation); 3) Global performance initiation and 4) Global performance refinement, with distinct thresholds of skill mastery freeing-up mental capacity for further learning goals. Narrative evidence on affective state, cognitive framework and learning environment is shown for each phase (Table 1 ). Time spent in each phase varied depending on self-efficacy, confidence, prior experiences, case intensity and local training support. Conclusion: Qualitative investigation provides important detail on learning needs of trainees at varying stages of the UGIE learning pathway. These vary considerably over time and trainers need to be aware of affective and cognitive factors and adjust techniques and training environment to optimise skills development. Disclosure of interest: None Declared. References: Ward ST, et al . Gut 2014;63:1746–1754 Burnard P, et al . Br Dental J. 2008;204:429–432